Mandatory Sick Pay Provision: A Labor Market Experiment - Stefan Bauernschuster; Peter Duersch; Jörg Oechssler; Radovan Vadovic (University of Heidelberg, Department of Economics, 2010)
Sick-pay is a common provision in labor contracts. It insures workers against a sudden loss of income due to unexpected absences and helps them smooth consumption. Therefore, many governments find sick-pay socially desirable and choose to mandate its provision. But sick-pay is not without its problems. Not only it suffers from moral hazard but more importantly it is subject to a potentially serious adverse selection problem (higher sick-pay attracts sicker workers). In this paper we report results of an experiment which inquires to the extend and the severity of the adverse selection when sick-pay is voluntary versus when it is mandatory. Theoretically, mandating sick-pay may be effective in diminishing adverse selection. However, our data provide clean evidence that counteracting effects are more salient. Mandatory sick pay exacerbates moral hazard problems by changing fairness perceptions and, as a consequence, increases sick pay provision far above the mandatory levels.
urn:nbn:de:bsz:16-opus-105430
Keywords: C9; C7; J3; 330; sick pay; sick leave; experiment; gift exchange; Lohnfortzahlung; Pflichtversicherung; Betriebliche Sozialleistungen; Leistungsmotivation; Austauschtheorie; Test